The Effect of Religion on Individual and Social Identity from the Perspective of Al-Farabi and Kierkegaard - Jalil Jalili (Journal of Philosophical Investigations)
This research examines and compares the views of Al-Farabi, an Islamic philosopher, and Søren Kierkegaard, a Danish philosopher and pioneer of Christian existentialism, on the role of religion in the formation of individual and social identity. The main goal of this research is a comparative analysis of the effects of religion on identity from two different perspectives. The research method is a comparative content analysis based on reliable sources and the main texts of philosophers. Al-Farabi sees religion as a social institution that strengthens the unity and cohesion of society and helps to educate virtuous people. He emphasizes the importance of religious and philosophical leaders in guiding society towards perfection, and believes that religion and reason complement each other. In contrast, Kierkegaard emphasizes the personal and inner experience of religion and considers religion a path to finding the meaning of life and facing existential anxieties. He believes that religion must be experienced individually and directly in order to form a meaningful and authentic identity. The results of this study show that both philosophers emphasize the fundamental importance of religion in the formation of individual and social identity, but they have different approaches and analyses on this issue. Al-Farabi's views are more focused on the social and political role of religion and the upbringing of virtuous people, while Kierkegaard's views are focused on the individual and inner experience of religion and dealing with existential challenges. These differences indicate that both views give a high status to the role of religion in determining human identity.